Integrated motor drives: state of the art and future trends - Abebe, Robert; Vakil, Gaurang; Lo Calzo, Giovanni; Cox, Thomas; Lambert, Simon; Johnson, Christopher Mark; Gerada, C.; Mecrow, Barrie (Institution of Engineering and Technology, 2016)
With increased need for high power density, high efficiency and high temperature capabilities in Aerospace and Automotive applications, Integrated Motor Drives (IMD) offers a potential solution. However, close physical integration of the converter and the machine may also lead to an increase in components temperature. This requires careful mechanical, structural and thermal analysis; and design of the IMD system. This paper reviews existing IMD technologies and their thermal effects on the IMD system. The effects of the power electronics (PE) position on the IMD system and its respective thermal management concepts are also investigated. The challenges faced in designing and manufacturing of an IMD along with the mechanical and structural impacts of close physical integration is also discussed and potential solutions are provided. Potential converter topologies for an IMD like the Matrix converter, 2-level Bridge, 3-level NPC and Multiphase full bridge converters are also reviewed. Wide band gap devices like SiC and GaN and their packaging in power modules for IMDs are also discussed. Power modules components and packaging technologies are also presented.